Newcomer challenges with accessing healthcare services in Saskatchewan, Canada - Lane , Ginny; Hengstermann , Mayari; White , Judy; Vatanparast, Hassan (Border Crossing, 2021)
Newcomers experience a variety of barriers to healthcare services. The study objective is to identify newcomers’ healthcare barriers. During 2014-2015, we conducted in-depth interviews with service providers, and newcomer parents who had been in Saskatchewan for under 5 years. Primary themes include: 1) navigation difficulty, 2) limited awareness, 3) language, 4) interpretation and translation, 5) health benefits, 6) service limitations and stigma, 7) gender and cultural concerns, 8) health attitudes and beliefs, and 9) work demands. The results exposed service gaps and suggest options to improve access to healthcare. Consideration should be given to the development of formal processes to ensure the provision of information concerning healthcare and health benefit programs, as well as responsive healthcare services, including convenient primary healthcare sites that offer comprehensive care in a culturally responsive manner with embedded interpretation services to ensure that the Saskatchewan healthcare system does not perpetuate or create health disparities.